Criminal Justice Forecasts of Risk A Machine Learning Approach - Berk, Richard; SpringerLink (Online service) (New York, NY : Springer New York, 2012)
n/a
Getting Started -- Some Important Background Material -- A Conceptual Introduction to Classification and Forecasting -- A More Formal Treatment of Classification and Forecasting -- Tree-Based Forecasting Methods -- Examples -- Implementation -- Some Concluding Observations About Actuarial Justice and More -- References.
Keywords: Computer science; Artificial intelligence; Mathematical statistics; Computer Science; Artificial Intelligence (incl. Robotics).; Statistical Theory and Methods; Probability and Statistics in Computer Science